2020
DOI: 10.1111/apt.15758
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic, anti‐depressant and other medication use is associated with clinically relevant oesophageal manometric abnormalities

Abstract: Background: Medications can affect gastrointestinal tract motility. However, their effects on oesophageal motility in particular are often not as widely known or may be underestimated. Aim:To review the effect of existing medication use on high-resolution oesophageal manometry (HRM) in a 'real-world' setting.Methods: Adult patients with upper gut symptoms and normal endoscopy or imaging who had HRM over a 22-month period were analysed. Achalasia and major disorders of peristalsis were excluded. All medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Serotonin and norepinephrine reuptake inhibitors are antidepressants and act by binding to the serotonin and norepinephrine transporters (73). Serotonin and norepinephrine reuptake inhibitors also act in the lower esophageal function (Level 2b; Grade: B) (74,75). However, no study addresses their use in achalasia patients, and consequently, their use should be restricted to research protocols (Level 5; Grade: D).…”
Section: Serotonin and Norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin and norepinephrine reuptake inhibitors are antidepressants and act by binding to the serotonin and norepinephrine transporters (73). Serotonin and norepinephrine reuptake inhibitors also act in the lower esophageal function (Level 2b; Grade: B) (74,75). However, no study addresses their use in achalasia patients, and consequently, their use should be restricted to research protocols (Level 5; Grade: D).…”
Section: Serotonin and Norepinephrine Reuptake Inhibitorsmentioning
confidence: 99%
“…Opioids inhibit excitatory neurotransmitter release (76), and benzodiazepines inhibit smooth muscle contraction (77). Benzodiazepines and opioids are associated with elevated integrated relaxation pressure (Level 1b; Grade: A) (75,78). However, no study addresses their use in achalasia patients, and their administration should be considered only for research protocols (Level 5; Grade: D).…”
Section: Benzodiazepines and Opioidsmentioning
confidence: 99%
“…38 A recent study from 2020 using HRM found calcium channel blockers were associated with a lower distal contractile integral (DCI). 39 Further study is needed to evaluate the impact of nifedipine and diltiazem on HRM using updated Chicago classification version 4.0 criteria for hypercontractile esophagus and DES.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…46 Most recently a study of 502 patients undergoing HRM found patients taking anticholinergics were more likely to have IEM (OR 3.6, CI 1.2-10.8) and patients taking TCAs were more likely to have esophagogastric outflow obstruction (OR 2.8, CI 1.1-7.0). 39…”
Section: Anticholinergic Agentsmentioning
confidence: 99%
“…19 Other medications including anticholinergics, serotonin/norepinephrine reuptake inhibitors (SNRI), benzodiazepines, and tricyclic antidepressants have also been associated with EGJOO but are not as well-studied. 20…”
Section: Egjoo Symptoms Classification and Differential Diagnosismentioning
confidence: 99%